Mapping the Religious Response of the Disaster-Hit Community: (Redefinition of Relationship between Human, God, Nature and Religion in Disaster Construction) - Ibnu Mujib (Al-Albab, 2015)
This paper would like to map the religious response in a post-disaster community. In an academic discourse, a post-disaster community is one with abnormal conditions, including how it defines aspects of Divinity in their religious perspective. Thus, the complexity of issues that encompass a disaster-hit community will shape the worldview, perspective, and the understanding of the relationship between human, God, nature, and religion, serves as the basic assumption of this research. So, there are several points that will be introduced in this paper including: first, the disaster typology from the perspective of the experts; second, the debate between the divine law and the law of nature in the context of disaster; and third, the religious response of the disaster-hit community over the history of the events of disaster. The research shows some important findings including the emergence of various forms of response about the events of disaster and their relation to human, God, nature, and religion itself. Since the concepts of disaster appear from a post-disaster society, on one side also require relationship which is able not only to respond to disasters but also to provide constructive solutions to the survival of the post-disaster community. Therefore, the stronger the religious normative doctrine of a person, the more difficult to bring closer to the context his survival not to mention life improvement. Nevertheless, in the majority of other communities that culturally experienced two sides of mass dilemma i.e. the theological concept of submission, patience, and gratitude in the religious worldview of post-disaster community as the disaster not only happened to a person but also to many people.